(untitled) (Studia Prawnicze / The Legal Studies, 1980)
Chapter I deals with the capacity of the EEC to conclude agreements and discusses the problem of concurring competences of the member States. The EEC Treaty does not contain a provision granting general treaty-making power but specifies only the functions of the particular organs in this proce’ss. In effect, the problem arises in delimitating the competence of the EEC to conclude agreements in specific fields from the concurring competence of the member States. Also controversial is the question of the direct binding force with respect to the EEC member States of agreements concluded between the EEC and third States. The Author submits that in case of agreements concluded by the EEC and signed and ratified as well by the member States the latter should be considered as separate parties to the agreement. If, however, the agreement has been concluded solely by the EEC, the member States are obliged under the EEC Treaty to recognize such an agreement as binding on them. In chapter II the subject-matter of agreements is presented. According to the Treaty the EEC is competent to conclude: 1) trade agreements, 2) Association agreements, 3) cooperation agreements with other organizations. Further competences may be presumed on the basis of article 235 of the Treaty. Since 1970 the EEC is exclusively competent to conclude agreements of commercial character. Preferencial agreements were concluded with all West European coun¬tries as well as with the majority of the African and Caribean countries. As till now no general agreement of commercial character was concluded with the CMEA countries, the USA and Japan. The EEC concluded a number of Association agreements in various spheres with particular countries and the groups of countries. Moreover, the EEC Commission concluded several agreements with other international organizations. The third chapter deals with the procedure of concluding agreements. This pro-cedure was regulated neither in the EEC Treaty nor in the regulations of particular organs. According to the common opinion, the Council is authorized to decide whether to open negotiations which are conducted by the Commision. In cases when the countries are also parties to an agreement, their representatives are also present and sometimes also the representatives of the Council. A negociated text of an agreement is approved by the Council by a formal decision. If the agreement is concluded by way of more complex preceedings, after signing it a consent to be bound by this agreement must be proclaimed by way of a distinct act and notification of the other party is necessary.